ANALYSIS OF CORPORATE PERFORMANCE MEASUREMENT WITH BALANCED SCORECARD CONCEPT (Case Study of PT. ADIRA INSURANCE) - Caesar Carry Augustinus Simanungkalit (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objective of this case study research is to measure the performance of PT. Adira Insurance using four perspectives of balanced scorecard, namely financial, customer, internal business process, and learning and growth. This research uses three-year data from 2014 until 2016. This research describes the state of the object being studied based on facts obtained from data collection, processing, presentation, and analysis. The results of the measurement show that the performance of PT. AdiraInsurance is quite good with the total score of 0.55, shown by the fact that its ROA reaches the target of above 1.5%, its NPM fluctuates every year, its current ratio does not reach the target of below 2x, and its BOPO is positive under 83%. From customer’s perspective, its customer retention indicators decline each year, its customer acquisition increases every year, its customer satisfaction fluctuates every year, and its customer profitability increases every year. From internal business process’ perspective, its AETR indicator has a positive result as it rises year by year. From learning and growth perspective, its employee retention indicator has positive a result due to decreases in every year, while its employee productivity fluctuates. After implementing balanced scorecard, PT. Adira Insurance becomes long-term oriented. The company also knows when to make major investments to understand customer’s needs and identify future attractive customer segments. The company should apply balanced scorecard in measuring its performance to get more comprehensive measurement results from the four perspectives, so the company can maintain its competitiveness in global market where the competition is higher. Keywords: balance scorecard, bsc, financial perspective, customer  perspective, internal and business perspective, learning and growth perspective.